How exosomal platelet-derived miRNAs can lead to spontaneous osteoclastogenesis in osteoporosis: a new mechanistic viewpoint - Salamanna, Francesca; Giavaresi, Gianluca; Di Martino, Alberto; Gaudio, Agostino; Nucera, Fabiana; Faldini, Cesare; Fini, Milena (Frontiers in Medicine, 2025)
Osteoporosis is a chronic bone disease characterized by impaired bone remodeling and increased fracture risk. While classical mechanisms implicate estrogen deficiency, aging, and altered receptor activator of the nuclear factor-κB ligand (RANKL)/osteoprotegerin (OPG) signaling, growing evidence supports a pivotal role of immune and inflammatory pathways in sustaining osteoclast-mediated bone resorption. A distinctive hallmark observed in osteoporotic patients is spontaneous osteoclastogenesis (SO), defined as the ability of mononuclear precursors to differentiate into osteoclasts even in the absence of exogenous stimuli such as RANKL or macrophage colony-stimulating factor (M-CSF), a process driven by an intrinsically primed in vivo microenvironment that includes platelets. We hypothesize that platelets may contribute to this priming not only through soluble mediators but also via the release of extracellular vesicles, particularly exosomes enriched in regulatory microRNAs (miRs). Within this framework, platelet-derived exosomal miRs (P-EXO-miRs) may orchestrate multiple intercellular interactions within the bone marrow microenvironment, modulating monocytes, macrophages, stromal and endothelial cells, as well as T and B lymphocytes. Specifically, miR-21, miR-223, miR-214, and miR-155 emerge as key candidates capable of regulating cytokine secretion, inflammatory signaling, and the RANKL/OPG balance, thereby promoting a pro-osteoclastogenic milieu. Network-based analysis using miRNet further supports the involvement of these miRs in pathways such as Hedgehog, Wnt, and actin cytoskeleton regulation, all relevant to osteoclast differentiation and function. Through these mechanisms, P-EXO-miRs may amplify chronic low-grade inflammation and facilitate spontaneous osteoclast differentiation and activity, ultimately contributing to bone loss in osteoporosis. Future investigations should aim to experimentally validate this platelet–bone axis, delineate the molecular targets of individual miRs, and explore their potential as circulating biomarkers or therapeutic targets. By unveiling this previously unrecognized role of platelet-derived miRs in SO, this hypothesis opens new perspectives for the understanding, early detection, and treatment of osteoporosis.